Atypical Pharmacodynamic Properties and Metabolic Profile of the Abused Synthetic Cannabinoid AB-PINACA: Potential Contribution to Pronounced Adverse Effects Relative to Δ9-THC - Hutchison, Rachel D.; Ford, Benjamin M.; Franks, Lirit N.; Wilson, Catheryn D.; Yarbrough, Azure L.; Fujiwara, Ryoichi; Su, Mark K.; Fernandez, Denise; James, Laura P.; Moran, Jeffery H.; Patton, Amy L.; Fantegrossi, William E.; et al. (Frontiers in Pharmacology, 2018)
Recreational use of marijuana is associated with few adverse effects, but abuse of synthetic cannabinoids (SCBs) can result in anxiety, psychosis, chest pain, seizures and death. To potentially explain higher toxicity associated with SCB use, we hypothesized that AB-PINACA, a common second generation SCB, exhibits atypical pharmacodynamic properties at CB1 cannabinoid receptors (CB1Rs) and/or a distinct metabolic profile when compared to ∆9-tetrahydrocannabinol (∆9-THC), the principal psychoactive cannabinoid present in marijuana. Liquid chromatography tandem mass spectrometry (LC/MS) identified AB-PINACA and monohydroxymetabolite(s) as primary phase I metabolites (4OH-AB-PINACA and/or 5OH-AB-PINACA) in human urine and serum obtained from forensic samples. In vitro experiments demonstrated that when compared to ∆9-THC, AB-PINACA exhibits similar affinity for CB1Rs, but greater efficacy for G-protein activation and higher potency for adenylyl cyclase inhibition. Chronic treatment with AB-PINACA also results in greater desensitization of CB1Rs (e.g., tolerance) than ∆9-THC. Importantly, monohydroxy metabolites of AB-PINACA retain affinity and full agonist activity at CB1Rs. Incubation of 4OH-AB-PINACA and 5OH-AB-PINACA with human liver microsomes (HLMs) results in limited glucuronide formation when compared to that of JWH-018-M2, a major monohydroxylated metabolite of the first generation SCB JWH-018. Finally, AB-PINACA and 4OH-AB-PINACA are active in vivo, producing CB1R-mediated hypothermia in mice. Taken collectively, the atypical pharmacodynamic properties of AB-PINACA at CB1Rs relative to ∆9-THC (e.g., higher potency/efficacy and greater production of desensitization), coupled with an unusual metabolic profile (e.g., production of metabolically stable active phase I metabolites) may contribute to the pronounced adverse effects observed with abuse of this SCB compared to marijuana.